2009
DOI: 10.1007/s12237-009-9186-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity, Not Adaptation to Salt Level, Explains Variation Along a Salinity Gradient in a Salt Marsh Perennial

Abstract: Evolutionary ecologists have long been intrigued by the fact that many plant species can inhabit a broad range of environmental conditions and that plants often exhibit dramatic differences in phenotype across environmental gradients. We investigated responses to salinity treatments in the salt marsh plant Borrichia frutescens to determine if the species is responding to variation in edaphic salt content through phenotypic plasticity or specialized trait response. We grew seedlings from fruits collected in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 54 publications
4
37
0
Order By: Relevance
“…ratio in the roots when exposed to high salinity and thus a similar response among populations to natural spatial salinity variation. Differences in salt tolerance has been shown to be both persistent (McNaugton 1966;Hester et al 1996Hester et al , 1998Hester et al , 2001 and plastic (Richards et al 2010), with genetic potential setting the limits and plasticity regulating the expression within those limits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ratio in the roots when exposed to high salinity and thus a similar response among populations to natural spatial salinity variation. Differences in salt tolerance has been shown to be both persistent (McNaugton 1966;Hester et al 1996Hester et al , 1998Hester et al , 2001 and plastic (Richards et al 2010), with genetic potential setting the limits and plasticity regulating the expression within those limits.…”
Section: Discussionmentioning
confidence: 99%
“…Spartina alterniflora grown from seed collected from high latitudes within their invasive range of China had greater rhizosphere bacterial diversity than populations from lower latitudes (Nie et al 2010). However, several traits can be environmentally controlled exhibiting plastic responses to local environmental gradients (e.g., Gallagher 1975;Trnka and Zedler 2000;Castillo et al 2005;Richards et al 2010). Additional studies are necessary to examine the persistence of traits that influence ecological function that have the potential to change with climate and environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…It remains unresolved, for instance, whether the extreme differences in plant phenotypes at the ends of salt marsh gradients are due to phenotypic plasticity in response to environmental variation or to specialized traits that have resulted from natural selection (Pennings and Bertness 2001). Richards et al (2010) address this type of question in a dominant salt marsh plant on Sapelo Island, Georgia, the Sea Ox-eye daisy, Borrichia frutescens. Using replicates of genetically different individuals in a greenhouse experiment, they found that trait response was due largely to phenotypic plasticity in every trait measured, and, in general, they found no evidence for adaptation to salt content alone.…”
Section: How Is Genetic Variation Relevant To Estuarine Science?mentioning
confidence: 99%
“…Reciprocal transplants and common garden experiments could be used to investigate whether long-lived perennials such as U. paniculata respond to microhabitat differences through the process of local adaptation versus phenotypic plasticity (Kawecki and Ebert 2004;Richards et al 2010). The responses we documented following the storm overwash events may have been driven by selective conditions affecting recruitment and establishment of particular genotypes.…”
Section: Discussionmentioning
confidence: 99%